Efeito da política contingenciamento da crise hídrica de 2014-2015 na região metropolitana de São Paulo no consumo residencial de água - Isabel Akemi Bueno Sado (2021)
The 2014 - 2016 water shortage crisis in the Metropolitan Region of São Paulo - RMSP raised questions about the impacts of regulatory contingency policies due to the nature of water resources: an essential good for the maintenance of life whose market is characterized by the strong presence of failures such as the formation of natural monopolies and the generation of externalities. These factors motivated the evaluation of the impact on residential water consumption in the RMSP between 2014 and 2016 in light of the tariff policy adopted by the regulatory agency. The measurement of the policy effects is done. By cross-referencing SABESP commercial data with IBGE indicators, it is possible to observe that the reduction in water consumption was more expressive in the following cases: connections categorized as slum; higher income classes; economies with individualized metering and that have sewage collection service. Regression techniques with hierarchical models were used to control for region-related effects resulting in different price elasticity behaviors from the traditional ordinary least squares model. The results of the elasticity of average prices charged per cubic meter proved consistent with negative and inelastic values. The results point to regional effects of census sectors on the variability of consumption on the order of 28% and that can reach 62% if explanatory variables of regional aggregates are included in the modeling. Income, however, was not an impacting factor on consumption variations due to the atypical behavior of multifamily dwellings. These peculiarities also affected the relevance of the vulnerability index, which represented only 3% of the variability in water consumption.